A Content-Based Filtering Approach for Matching Village Potentials with Community Service Programs - Sarja, Ni Luh Ayu Kartika Yuniastari; Indrawan, I Kadek Surya; Putrawan, Agus Adi; Sarja, Ni Ketut Pradani Gayatri (Indonesian Scientific Journal, 2025)
Village development through the development of village potential is carried out by universities in the form of community service. With the community service program, it is expected to help villages in village development so that they can become independent villages. However, in its implementation, the designed assistance programs are not specific and not aligned with the needs and potential of the village. As a result, the assistance provided is less effective and having minimal impact on village development. One of the causes is the unavailability of data on village potential and problems systematically and structured. Based on these problems, a recommendation system is needed that is able to provide assistance program proposals that are in accordance with the potential and problems of the village specifically and relevantly. This research uses Content-Based Filtering which provides recommendations based on the similarity of input data content with available historical data. The purpose of this research is to make the planning and implementation process of village assistance programs more efficient, effective, and on target. The results of the research are that the Content-Based Filtering method has proven effective in providing recommendations that are appropriate for mapping village potential and village assistance programs.